The efficacy of traditional chinese medicine combined with hyperthermic intraperitoneal chemotherapy for malignant ascites: A systematic review and meta-analysis - Lin, Zhixian; Chen, Jiangfeng; Liu, Yunxia (Frontiers in Pharmacology, 2022)
Objective: Malignant ascites (MA) is a common complication of terminal cancer, which seriously affects the life quality and prognosis of patients. Both hyperthermic intraperitoneal chemotherapy (HIPEC) and traditional Chinese medicine (TCM) preparations have achieved significant efficacy in the treatment of MA. The treatment strategy of TCM combined with HIPEC has been gradually promoted and applied in China. The purpose of this systematic review and meta-analysis was to assess the efficacy of TCM combined with HIPEC in the treatment of MA. Methods: Randomized controlled trials (RCTs) of TCM combined with HIPEC for MA were searched from 7 electronic databases. Two researchers used the Cochrane Collaboration’s tool to assess the risk of bias. Excel 2019 was used to establish a database for information extraction, RevMan 5.4 software was used to analyze the included test data, and STATA v16.0 was used to conduct Egger's test to further detect publication bias. Results: A total of 19 studies involving 1504 patients were included in this meta-analysis. The results showed that compared with the single use of HIPEC, TCM combined with HIPEC could significantly improve the clinical efficacy (RR=1.51, 95%CI [1.40, 1.63], P <0.00001) and karnofsky performance status (KPS) score (MD=8.16, 95%CI [6.46, 9.85], P <0.00001), reduce the ascites volume (MD=-156.98, 95%CI [-213.71, -100.25], P <0.00001). However, there was no statistical significance in reducing abdominal circumference between TCM combined with HIPEC and HIPEC alone (MD=-1.8, 95%CI [-4.57, -0.97], P =0.2). Conclusion: This study found that TCM combined with HIPEC had a beneficial therapeutic effect on MA. However, more standard, double-blind, multicenter RCTs are needed to further confirm the efficacy of TCM combined with HIPEC in the treatment of MA.